Ras Oncogene-Mediated Progressive Silencing of Extracellular Superoxide Dismutase in Tumorigenesis. (15th October 2015) - Cammarota, Francesca; de Vita, Gabriella; Salvatore, Marco; Laukkanen, Mikko O.
Abstract : Extracellular superoxide dismutase (SOD3) is a secreted enzyme that uses superoxide anion as a substrate in a dismutase reaction that results in the formation of hydrogen peroxide. Both of these reactive oxygen species affect growth signaling in cells. Although SOD3 has growth-supporting characteristics, the expression of SOD3 is downregulated in epithelial cancer cells. In the current work, we studied the mechanisms regulating SOD3 expression in vitro using thyroid cell models representing different stages of thyroid cancer. We demonstrate that a low level of RAS activation increases SOD3 mRNA synthesis that then gradually decreases with increasing levels of RAS activation and the decreasing degree of differentiation of the cancer cells. Our data indicate that SOD3 regulation can be divided into two classes. The first class involves RAS–driven reversible regulation of SOD3 expression that can be mediated by the following mechanisms: RAS GTPase regulatory genes that are responsible for SOD3 self-regulation; RAS-stimulated p38 MAPK activation; and RAS-activated increased expression of the mir21 microRNA, which inversely correlates with sod3 mRNA expression. The second class involves permanent silencing of SOD3 mediated by epigenetic DNA methylation in cells that represent more advanced cancers. Therefore, the work suggests that SOD3 belongs to the group of ras oncogene-silenced genes.